Complex aortic arch anomaly: Right aortic arch with aberrant left subclavian artery, fenestrated proximal right and duplicated proximal left vertebral arteries—CT angiography findings and review of the literature. Issue 4 (August 2015) - Tong, Elizabeth; Rizvi, Tanvir; Hagspiel, Klaus D
Congenital aortic arch and vertebral artery anomalies are a relatively rare finding discovered on imaging either incidentally or for evaluation of entities like dysphagia or subclavian steal. Right aortic arch is an uncommon anatomical anomaly that occurs in less than 0.1% of the population, and in half of these cases the left subclavian artery is also aberrant. 1 Unilateral vertebral artery (VA) duplication is rare with an observed prevalence of 0.72% in cadavers. 2 Fenestration of the VA is more common than duplication, with a prevalence of approximately 0.23%–1.95%. 3, 4 We describe the case of a 25-year-old female who was found to have a right aortic arch with aberrant left subclavian artery, duplicated left vertebral artery and a fenestrated right vertebral artery on CT angiography performed for evaluation of dysphagia. This combination of findings has not been reported before, to the best of our knowledge. We review the embryologic mechanism for the development of the normal aortic arch, right aortic arch, vertebral artery duplication and vertebral artery fenestration. The incidence of these entities, resultant symptoms and clinical implications are also reviewed. The increased associated incidence of aneurysm formation, dissection, arteriovenous malformations and thromboembolic events with fenestration is also discussed.